The Basic Concepts of Preparation and Presentation of Islamic Financial Statements - Dini Puspitasari; Siti Nurul Muhlisah; Meichio Lesmana; Muhamad Kharis Tambusai (University of Darusssalam Gontor, 2022)
The potential of Islamic banking continues to be enhanced to build a national sharia economic ecosystem, it's can contribute optimally to the national economy and social development. Operational principles and accounting standards are one of the foundations for progress in Islamic banking. An overview of the pros and cons of Islamic banking can be identified through its performance which is reflected in the financial statements. The focus of this paper is on the preparation and presentation of Islamic financial statements along with a comparison of financial statements between sharia and conventional, in which conventional financial statements contain fewer elements of financial statements. This type of research is library research which analyzes data with descriptive analysis. The results of this research indicate that Islamic financial statements are not only related to commercial aspects but also cover all aspects of human life, be it economic, political, social, or moral philosophy. In addition to reflecting Islamic banking activities, the Islamic financial statement also divides its rights and obligations as reported in the statement of financial position (balance sheet), income statement, cash flow statement, and changes in equity. But it also reflects as a mandate holder of social activity funds that are managed separately, which is reported in the report on the source and use of zakat funds and the report on the source and use of benevolent funds (qardhul hasan).Potensi perbankan syariah terus ditingkatkan untuk membangun ekosistem ekonomi syariah nasional, sehingga dapat berkontribusi secara optimal dalam perekonomian nasional dan pembangunan sosial. Prinsip-prinsip operasional dan standar akuntansi menjadi salah satu dasar kemajuan perbankan syariah. Gambaran tentang baik dan buruknya suatu perbankan syariah dapat dikenali melalui kinerjanya yang tergambar dalam laporan keuangan. Fokus tulisan ini adalah tentang penyusunan dan penyajian laporan keuangan syariah berikut dengan perbandingan laporan keuangan antara syariah dan konvensional. Jenis penelitian ini adalah penelitian kepustkaan (library research) dengan analisis data berupa metode deskriptif. Hasil penelitian ini menunjukkan bahwa laporan keuangan syariah merupakan laporan keuangan yang tidak hanya berhubungan dengan aspek komersial, tetapi juga mencangkup seluruh aspek kehidupan umat manusia, baik ekonomi, politik, sosial, dan filsafat moral. Laporan keuangan syariah selain mencerminkan kegiatan perbankan syariah yang membagi hak dan kewajibannya seperti yang dilaporkan dalam laporan posisi keuangan (neraca), laporan laba rugi, laporan arus kas, dan laporan perubahan ekuitas, juga mencerminkan sebagai pemegang amanah dana kegiatan sosial yang dikelola secara terpisah dan dilaporkan dalam laporan sumber dan penggunaan dana zakat dan laporan sumber dan penggunaan dana kebajikan (qardhul hasan).